Organic C distribution and N mineralization in soil of oak woodlands with improved pastures - Gómez-Rey, Maria Xesús; Garcês, Ana; Madeira, Manuel (Revista de Ciências Agrárias, 2011)
Cork oak woodlands in Portugal are a multipurpose agroforestry system occurring in areas mostly degraded by former cereal crops and overgrazing. The objective of this study was to evaluate the effect of scattered cork oak trees (Quercus suber L.) on soil quality, considering two land use systems: unmanaged pastures and improved pastures. Soil samples were collected in a square grid around scattered cork oak trees to evaluate the spatial variability of soil bulk density and chemical properties. In soil samples taken beneath tree canopy and in the open, net N mineralization was evaluated by aerobic incubations. Also, laboratory incubations were carried out to evaluate the effect of roots (tree or/and herbaceous) and water solutions (bulk precipitation, throughfall or stemflow) on net N mineralization.Contents of organic C, total N and extractable P were increased beneath the tree canopy, and gradually decreased with the increase of distance to the tree trunk. Improved pastures established 26 years ago increased organic C (0.76 kg m-2), total N (0.06 kg m-2) and extractable P (2.70 g m-2) amounts in the 0-10 cm soil layer beneath the tree canopy relatively to those of unmanaged pastures. Net N mineralization was significantly greater (about 2 times) in soils beneath the tree canopy than in those of open areas. N mineralization was unaffected by addition of throughfall or stemflow, while a significant reduction resulted from tree roots addition, this effect being stronger for herbaceous plant roots than for tree roots. Maintenance of tree cover combined with permanent improved pastures should be considered to improve soil quality in oak woodlands of Southern Portugal.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: agroforestry systems; legumes; Mediterranean climate; soil quality.